1985
DOI: 10.1002/ajmg.1320220217
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 14 mosaicism with t(14;15)(q11;p11) in offspring of a balanced translocation carrier mother

Abstract: A 2-year-old girl with growth and developmental retardation, minor facial anomalies, asymmetry of face and body, tetralogy of Fallot, and reticular hyperpigmentation of the skin was found to have mosaic trisomy 14 involving a t(14;15)(q11;p11). The patient showed mosaicism for 46,XX cell line, apparently resulting from a break of the translocation chromosome and a subsequent loss of 14q. The mother has a balanced translocation t(14;15)(q11;p11). Inherited trisomy 14 has not been reported previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…The percentage ranged from <1 to 16%. The patient reported by Fujimoto et al [1985] had the trisomic cells in the skin obtained from the right arm, the atrophic side, and no trisomic cells in the skin from the left arm. one patient.…”
Section: Patient Pd [Johnson Et Al 19791mentioning
confidence: 95%
“…The percentage ranged from <1 to 16%. The patient reported by Fujimoto et al [1985] had the trisomic cells in the skin obtained from the right arm, the atrophic side, and no trisomic cells in the skin from the left arm. one patient.…”
Section: Patient Pd [Johnson Et Al 19791mentioning
confidence: 95%
“…The most common type of abnormal cell line resulting in trisomy 14 mosaicism is free trisomy 14, found in 58% (14/24), followed by isochromosome 14q in 21% (5/24). Other abnormal cell lines reported include translocation (14;15) [Fujimoto et al, 1985] and dicentric chromosome 14 with a ''mirror image'' duplication resulting in trisomy for the entire chromosome 14 [Tunca et al, 2000]. Two abnormal cell lines resulting in mosaicism have also been reported [Jenkins et al, 1981;Antonarakis et al, 1993;Tzoufi et al, 2007;Becerra et al, 2008].…”
mentioning
confidence: 90%
“…(A) Rethoré et al [1975]; (B) Martin et al [1977]; (C) Johnson et al [1979]; (D) Turleau et al [1980]; (E) Jenkins et al [1981]; (F) Dallapicola et al [1984]; (G) Ozawa et al [1984]; (H) Petersen et al [1986]; (I) Fujimoto et al [1985]; (J) Kaplan et al [1986]; (K) Lipson [1987]; (L) Cheung et al [1988]; (M) Vachvanichsanong et al [1991] A more detailed list of reported anomalies may be obtained from the authors. a F/u by Fujimoto et al [1992].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The hypo-or hyperpigmented lines often follow Blaschko lines on the back and the limbs. It is now clear that the disorder represents mosaicism of 2 kinds of melanocytes with different pigmentary potentials, due to genetic or chromosomal mosaicism or chimerism [Findlay and Moores, 1980;Hall, 1988;Thomas et al, 1989;Flannery, 19901. Interest in chromosomal analysis of the individuals with pigmentary dysplasia was aroused in 1985, when its association with chromosomal mosaicism was confirmed [Flannery et al, 1985;Fujimoto et al, 1985;Ishikawa et al, 1985;Miller and Parker, 19851. We are aware of at least 53 individuals with the disorder chromosomally analyzed since then.…”
Section: Introductionmentioning
confidence: 99%